Mitochondria-controlled signaling mechanisms of brain protection in hypoxia - Lukyanova, Ludmila D.; Kirova, Yulia I. (Frontiers in Neuroscience, 2015)
The article is focused on the role of the cell bioenergetic apparatus, mitochondria, involved in development of immediate and delayed molecular mechanisms for adaptation to hypoxic stress in brain cortex. Hypoxia induces reprogramming of respiratory chain function and switching from oxidation of NAD-related substrates (complex I) to succinate oxidation (complex II). Transient, reversible, compensatory activation of respiratory chain complex II is a major mechanism of immediate adaptation to hypoxia necessary for 1) succinate-related energy synthesis in the conditions of oxygen deficiency and formation of urgent resistance in the body; 2) succinate-related stabilization of HIF-1α and initiation of its transcriptional activity related with formation of long-term adaptation; 3) succinate-related activation of the succinate-specific receptor, GPR91.This mechanism participates in at least four critical regulatory functions: 1) sensor function related with changes in kinetic properties of complex I and complex II in response to a gradual decrease in ambient oxygen concentration; this function is designed for selection of the most efficient pathway for energy substrate oxidation in hypoxia; 2) compensatory function focused on formation of immediate adaptive responses to hypoxia and hypoxic resistance of the body; 3) transcriptional function focused on activated synthesis of HIF-1 and the genes providing long-term adaptation to low рО2; 4) receptor function, which reflects participation of mitochondria in the intercellular signaling system via the succinate-dependent receptor, GPR91. Inallcases, the desired result is achieved by activation of the succinate-dependent oxidation pathway, which allows considering succinate as a signaling molecule. Patterns of mitochondria-controlled activation of GPR-91- and HIF-1-dependent reaction were considered, and a possibility of their participation in cellular-intercellular-systemic interactions in hypoxia and adaptation was proved.